Faktor Kebudayaan dalam Teori Hubungan Internasional [The Cultural Factors in International Relations Theory] - Umar Suryadi Bakry (Verity: Jurnal Ilmiah Hubungan Internasional (International Relations Journal), 2017)
This article tries to explain some thoughts on the importance of cultural factors in the study of International Relations (IR).  The mainstream theories of international relations since the end of the World War II have ignored the role of cultural factors in world politics. But, after the Cold War era in 1990s, culture began to enter the center of research on international relations.  After the Cold War ended, cultural factors become particularly prominent and began to gain more attention from the scholars of International Relations. There are at least three prominent theories which are increasingly taking into account the role of cultural factors in international relations, that is, Huntington’s “clash of civilization” theory, Nye’s “soft power” theory, and constructivism theory. In addition, since the 1990s, many studies conducted by IR scholars have focused on the relationship between culture and the foreign policy of a country. The emergence of international culturology as a sub-field of IR studies further confirms that culture is an important variable in international relations.